Digital Finance And Esg Convergence In Gold Markets: Technologies, Standards And Market Impacts - Sumadi (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The gold market has long served as a reliable store of value and a strategic hedge during periods of economic turbulence. In the digital age, the market is undergoing a profound transformation driven by financial technology innovation. Digital trading platforms, blockchain-based tokenization, and fintech solutions are redefining how investors buy, sell, and verify ownership of gold, enhancing both transaction speed and transparency. According to the World Gold Council (2022), digital channels now facilitate over 40% of global gold transactions, demonstrating the rapid expansion of digital finance in this sector. Sustainability challenges persist only about 10% of newly mined gold has traceable origin verification (OECD, 2021), limiting ESG compliance and eroding investor trust. Empirically examines how blockchain, fintech platforms, and artificial intelligence (AI) can enhance ESG integration, transparency, and traceability across the gold investment ecosystem. Using a mixed empirical analytical approach with secondary data from the World Gold Council (WGC), International Monetary Fund (IMF), and Scopus-indexed studies (2019–2024), the findings reveal that digital finance mechanisms increase ESG reporting accuracy by 38% and reduce transaction opacity by 27%. The integration of blockchain based auditing and AI driven ESG analytics strengthens accountability and investor confidence while promoting sustainable financial practices. The study offers a comprehensive theoretical empirical framework linking digital finance innovation with ESG outcomes, supporting a more transparent, ethical, and resilient global gold market.